ESTUDIO COMPARATIVO DEL ANÁLISIS CEFALOMÉTRICO POSTEROANTERIOR DE PADRES CON HIJOS CON LABIO Y/O PALADAR HENDIDO NO SINDRÓMICO Y DE PADRES CON HIJOS SIN HENDIDURA (2018)
Objective: To compare the posteroanterior cephalometric measures (PA) present in parents of children with cleft lip and/or palate and of parents of children without orofacial clefting (HOF).Materials and methods: A descriptive cross-sectional and observational study was done. Eighty two parents were selected: fourteen-three parents of children with non-syndromic LPH and 39 parents of children without HOF. Sociodemographic variables and PA cephalometric measures were included. The statistical analysis plan implied the calculation of summary measures and T student and rank Wilcoxon test were applied. PA x-rays of the two groups were obtained using a standard technique. Photos were taken using a digital camera, which were then exported to a computer previously calibrated and they were analyzed using the Software Nemoceph.Results: There were statistically significant differences between parents with and without orofacial fissures in the following variables: Cg-ENA, ENA-Me, Cg-Me, Ag-GA. Equally, there was statistical significance for gender in the presence of children with or without HOF in the variable Cg-ENA, ENA-Me, Cg-Me, Ag-GA, Bc-Me.Conclusions: Some PA cephalometric cranio-facial measures can be different between population with and without LPH, its importance in the development of the HOF will allow the evaluation of the risk of the presence of this anomaly in future generations.